Reaction of 1,5-bis (salicyladehyde) Carbohydrazone with Mn (II), Co (II) & Ni (II) Chlorides - Srivastava, Shekhar; Srivastava, Vanita (Asian Journal of Chemistry, 2010)
Nine complexes of MnCl2. CoCl2 and NiCl2 of the type MLCl2, M2LCl4 and ML2Cl2 (where L ═ 1, 5-bis (salicylaldehyde) carbohydrazone and M ═ Ni, Mn and Co) have been synthesised and characterised by elemental analysis, conductivity, IR and XPS data.